Dental fragment bonding as a technique in oral rehabilitation: literature review (Research, Society and Development, 2020)
Introduction: The frequency of dental fracture, as well as the difficulties to restore them properly have stimulated the development of restorative techniques and materials that provide aesthetics and function seemly to the natural dentition. One of the techniques that most provide aesthetics and function in a harmonious way to fractured anterior teeth is the fragment reattachment. Objective: The objective of this article was to review the available literature, to present the indications, advantages, limitations, classification, diagnostic criteria and selection of material and technique to be used to perform the fragment reattachment technique. Results: The present work is a bibliographic review research where it was carried out through the online library, in the PubMed and VHL databases of articles in addition to book chapters, in portuguese or english in the period from 1955 to 2019. 30 articles with full text in electronic support and that fit the inclusion / exclusion criteria and 5 books were selected. Conclusion: The use of the fragment bonding technique is an excellent, important and lasting alternative for the restoration of fractured anterior teeth, both from the aesthetic and functional point of view, as well as from the psychological point of view.